KESIAPAN PSIKOLOGIS MASYARAKAT PEDESAAN DAN PERKOTAAN MENGHADAPI DIVERSIFIKASI PANGAN POKOK - Hidayah, Nurul (HUMANITAS (Jurnal Psikologi Indonesia), 2011)
The purpose of this research was exploring psychological readinesstoward the diversification of primary food among rural and urban community.The subjects were the residences at Kecamatan Gedang Sari KabupatenGunungkidul and the residences at Kecamatan Gedongtengen KotaYogyakarta.Â Data were obtained through questionnaire tools, observationand interview. Analysis was done by qualitative analysis and descriptivestatistics. The result of this research indicated that: (1) the rate of knowledgeabout the diversification of primary food among urban people was higherthan rural people; (2) rural and urban people have the same positive attitudeto the diversification of primary food; (3) rural people have applied thediversification of primary food, but they still have extrinsic motivation; (4)urban people havenât been ready yetÂ to apply the diversification of primaryfood; (5) there was the difference of primary food variance among ruraland urban community; cassava was the rural peopleâs choice and wheatwas the urban peopleâs choice.